(untitled) (Heritage, 2025)
The aim of this study was to examine the predictive role of self-esteem and assertiveness in explaining negative affectivity (depressiveness, anxiety, and stress) in 382 high school students from Belgrade and Kosovska Mitrovica, while also considering gender differences. The study used self-esteem and assertiveness scales, as well as the DASS-21. Data were analyzed using Pearson correlation, t-tests, and hierarchical regression analysis. Self-esteem was found to be a strong and consistent negative predictor of depressiveness, anxiety, and stress in both samples. Assertiveness was a significant predictor only in the Belgrade sample. Adolescents from Kosovska Mitrovica had significantly lower self-esteem and higher levels of depressiveness and anxiety. Girls had significantly higher self-esteem and stress levels than boys. Self-esteem represents a key protective factor for adolescent mental health. The findings underscore the importance of sociocultural context and have implications for the development of targeted preventive programs.